Duchenne Muscular Dystrophy: Modern Approaches in Patient Management - Inga V. Anisimova; Svetlana B. Artemyeva; Elena D. Belousova; Nato D. Vashakmadze; Dmitriy V. Vlodavets; Tatiana A. Gremyakova; Olga S. Groznova; Valentina I. Guzeva; Elena V. Gusakova; Lyudmila M. Kuzenkova; Alexey L. Kurenkov; Sergey I. Kutsev; et al. (Union of pediatricians of Russia, 2023)
Duchenne muscular dystrophy is one of the most common forms of childhood muscular dystrophies. Its incidence is 1 in 3.5-6 thousand newborn boys according to various sources. The disease is caused by the mutation in the DMD gene coding the dystrophin protein, it leads to the dystrophin absence or malfunction. The disease is characterized by proximal muscle weakness and gastrocnemius muscles pseudohypertrophy. In average, patients lose the ability to walk by themselves by the age of 11 and become nonambulatory. The authors have present modern epidemiological data and etiopathogenesis features of Duchenne muscular dystrophy, and have described clinical signs of different disease stages. The algorithm and key points of differential diagnosis are indicated. Special attention was given to the patients' management: pathogenetic treatment and rehabilitation of pediatric patients.